A drum, deferred: Solomon Ilori in the New York jazz scene, 1958–1964 - Gazit, Ofer (Jazz Research Journal, 2020)
During the 1960s, West African musicians rattled the New York jazz scene, bringing new sounds to late-night jam sessions, recording studios, and jazz festivals. Jazz scholars have interpreted musical imaginations of Africa by American jazz musicians as a sign of pan-African solidarity and cultural affinity among musicians of African and Afrodiasporic ancestry. While these studies have been important in identifying the political implications of such collaborations for African American musicians, they underplay the complex positioning of West African immigrants in these contexts and the social and musical gaps that separate African immigrants from their American counterparts. Drawing on my work with composer and percussionist Solomon Ilori, one of the leading Yoruba musicians in New York and amongst the last living exponents of the African jazz scene of the 1960s, I use the notion of décalage to explore how linguistic, social and historical gaps are articulated in musical recordings and public concerts in the 1960s African jazz scene in New York. Originally coined by Léopold Senghor to describe a sense of discrepancy between Africans and African Americans, décalage allows me to show how different perceptions of time, as well as choice of repertoire, instrumentation, rhythmic patterns and melodic material complicate a notion of musical pan-Africanism. Moreover, it explicates the unique ways in which African immigrants reacted socially and musically to the boundaries they face in the US and its particular formations of national, racial and musical identity.